DIPG-12. Induced mitotic abnormalities associated with BMI-1 modulation sensitize diffuse intrinsic pontine glioma cells to ionizing radiation. (3rd June 2022) - Kumar, Shiva Senthil; Mishra, Deepak; Mchugh, Todd; Drissi, Rachid
Abstract: Diffuse intrinsic pontine glioma (DIPG) remains an incurable childhood brain cancer with a median overall survival of less than 12 months, affecting 200-300 children annually in the United States. Hence, there is an unmet need for the development of novel and effective targeted therapies. BMI-1 is a subunit of the multimeric protein complex Polycomb repressor complex 1 (PRC1) implicated in self-renewal of normal and cancer cells, and in DNA damage signaling. We have previously identified BMI-1 as a potential therapeutic target in DIPG and have shown that BMI-1 is highly expressed in DIPG tumors regardless of H3K27 mutational status. Treatment of DIPG cells with PTC596, a small molecule initially identified as a BMI-1 modulator, and ionizing radiation (IR) impairs the kinetics of DNA damage response. in vivo, treatment with PTC596 alone delayed tumor growth kinetics and induced in-tumor apoptosis. However, we observed tumor regrowth once PTC596 treatment is completed or discontinued. In the present study, we evaluated the use of PTC596 in combination with IR. Our in vivo results indicate that PTC596 sensitizes DIPG cells to IR inducing a prolonged cell growth arrest 14 days post-treatment compared to IR or PTC596 alone. The effectiveness of this combination is currently evaluated in murine orthotopic DIPG models and the results will be presented. PTC596 is being tested in newly diagnosed children with DIPG and high-grade gliomas (NCT03605550). Data collected from this study will support the development of a novel therapy including PTC596 in combination with radiotherapy to treat children with DIPG.